Typification of covariational reasoning patterns in engineering degree new students - Bojorquez Gutiérrez, Karla; González-Quiñones, Fidel; Tarango, Javier (IE Revista de Investigación Educativa de la REDIECH, 2021)
The goal of this article is to analyze the level of covariational reasoning in new students in the engineering career of a public higher education institution, presenting data that comes from a research with a sample of 215 students under a non-experimental, cross-sectional mixed approach, they answered a measurement instrument adapted from other instruments previously validated by their authors. The nature of the study allowed obtaining grades from each student based on the success or error in the interpretation of the variability of the concepts analyzed, but also shows a qualitative interpretation of the reasons for choosing their answer, making possible a more complete interpretation of the results of the applied test, which allowed to classify the subjects participating in the study in five different levels of reasoning and lead to identify consistencies between the way in which the selection of each graph is justified, as well as the condition reached and presented on the level of covariational reasoning, which shows a robust coordination as a finding.